From theory to practice, operating the clinical simulation in Nursing teaching - Saionara Nunes de Oliveira; Aline Massaroli; Jussara Gue Martini; Jeferson Rodrigues
ABSTRACT Objective: To report the experience of the operationalization of clinical simulation as a pedagogical strategy in a subject of an undergraduate course in Nursing. Method: Clinical simulation cycles were carried out following the steps of action research, such as: planning, action, observation and reflection, from March 2014 to July 2015 with 10 professors and 44 students from a Primary Care and Mental Health subject of an undergraduate course in Nursing. Results: Five cycles of clinical simulation were performed, at the end of each cycle modifications were suggested by students and professors and the operation was adjusted to meet the needs of the subject. The main points of change were: professor role, logistics, equipment, debriefing model and preparation of "simulated patients". Final considerations: The clinical simulation is a possible method to be operationalized in undergraduate course in Nursing, needs pedagogical and logistic planning as well as, sensitization of professors and students.